Indoor airborne bacteria and fungi at different background area in nurseries and day care centres environments - Mohd Nazri, Nur Shahidah; Shamsudin, Hasnah; Sumali, Shuhaili; Mohd. Din, Shamzani Affendy; Mohd Aris, Mohd Shukri (RAZI Publishing, 2017)
Respiratory symptoms among children cases increased dramatically was believe due to poor indoor air quality. Nursery and day care centre (DCC) appear to be the site of exposure and transmission of airborne microorganism between children. This study aims to assess the relation between the colony forming unit level of biological contaminant (bacteria and fungi) between urban and suburban location correlate with indoor air quality (IAQ) parameters. Besides, the other aims for this study were to identify the types of an airborne pathogenic microbial contaminant in the nursery and DCC. The airborne microbial sampling was done by using Surface Air System Indoor air Quality (SAS IAQ), which taken at the end of June until early August 2015. This study presents the diversity of indoor airborne bacteria and fungi in the nursery and DCC demonstrated in relation to occupancy, location, and ventilation system. Correlation between bacteria and fungi counts and the other IAQ parameters (temperature, RH, CO2, and CO) was unable to be studied due to instruments limitation. Counts of airborne bacteria and fungi were measured as colony forming units (CFU) grown on agar plates. CFU counts were compared by sampling sessions and sampling locations (babies room, a kindergarten room, and control room). Fluctuations in bacteria and fungi counts in such conditions were observed. Three groups of culturable bacteria were identified: Gram-positive cocci, Gram-positive bacilli, and Gram-negative bacteria while five genera of fungi successfully identified were Aspergillus, Penicillium, Rhizopus, MucorandChrysonilia. Certain bacteria isolated from this study were identified at a species level by 16s rRNA amplification including S. haemolyticus, A. baumannii, P. stutzeri, M. osloensis, M. luteus, B. subtilis, Rothia spp., and Roseomonasspp. Overall findings suggest that IAQ level in investigated sites was at poor level due to high bacteria and fungi concentrations with isolation of some opportunistic pathogenic microorganism. This pathogenic microorganism will cause adverse health reaction especially to young children. This study will provide a baseline of hygienic indoor air quality in nursery and day care centre.